1904
DOI: 10.1007/bf02979999
|View full text |Cite
|
Sign up to set email alerts
|

Über Hautsinnesorgane neben dem menschlichen Haar (Haarscheiben) und ihre vergleichend=anatomische Bedeutung

Abstract: Aus der hydrotherapeutischen Anstalt der Universit~t Berlin. 0ber Hautsinnesorgane neben dem menschlichen Haar (Haarscheiben) und ihre vergleichend-anatomische Bedeutung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

1925
1925
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(13 citation statements)
references
References 11 publications
1
11
0
1
Order By: Relevance
“…SAI units and touch spots It has been shown in animal experiments that SAL afferents supply clusters of Merkel cells that are located closely together below small spots of specialized epidermal structures forming touch spots in the hairy skin (Iggo & Muir, 1969). The structure of our SAI fields conforms very well to this pattern, assuming that each high-sensitivity spot corresponds to a single dome or touch spot, as originally described by Pinkus (1904). An additional detail, not previously described, was that many SAI fields had a very small spot in addition to the two to four regular touch spots.…”
Section: Methods Of Stimulationmentioning
confidence: 70%
See 1 more Smart Citation
“…SAI units and touch spots It has been shown in animal experiments that SAL afferents supply clusters of Merkel cells that are located closely together below small spots of specialized epidermal structures forming touch spots in the hairy skin (Iggo & Muir, 1969). The structure of our SAI fields conforms very well to this pattern, assuming that each high-sensitivity spot corresponds to a single dome or touch spot, as originally described by Pinkus (1904). An additional detail, not previously described, was that many SAI fields had a very small spot in addition to the two to four regular touch spots.…”
Section: Methods Of Stimulationmentioning
confidence: 70%
“…The spatial spike densities are indicated by a colour code in Fig. 5 that these spots correspond to the touch spots and domes covering clusters of Merkel cells as previously described in other mammals (Pinkus, 1904;Iggo & Muir, 1969). None of the eleven SAI units was spontaneously firing.…”
Section: Methodsmentioning
confidence: 99%
“…Vernon B. Mountcastle suggested that the excrescences of the stimulus points might be Haarscheiben, discs or dome-like structures first described by Pinkus (1,2) in the skin of man and later by Iggo (3) in the skin of cats and monkeys. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There are several confirmatory reports of the distinctive physiological properties of the afferent unit, particularly by Tapper (1965), Werner & Mountcastle (1965), Lindblom & Tapper (1966), and Smith (1968), in the cat, rabbit and monkey. As the results will show, the sense organ can now be identified with the 'hair disk' (Haarscheibe) of Pinkus (1904) (see Pinkus H., 1964, for a historical note) which has been found in 764 TOUCH CORPUSCLE 765 several species including man (Tamponi, 1939;Kawamura, 1954;Straile, 1958Straile, , 1960Straile, , 1961Winkelmann, 1959;Siminoff, 1965;Mann & Straile, 1965;Smith, 1968). In the past the afferent unit appears sometimes to have been confused with, or not distinguished from, another less numerous kind of slowly adapting cutaneous mechanoreceptor (Chambers & Iggo, 1967;Iggo, 1968), from which, however, it can now be distinguished on several grounds.…”
Section: Introductionmentioning
confidence: 97%